Nitrogen X-ray absorption in the local ISM. Issue 3 (28th April 2021) - Gatuzz, Efrain; García, Javier A; Kallman, Timothy R
ABSTRACT: Nitrogen is one of the most abundant metals in the interstellar medium (ISM), and thus it constitutes an excellent test to study a variety of astrophysical environments, ranging from nova to active galactic nuclei. We present a detailed analysis of the gaseous component of the N K-edge using high-resolution XMM–Newton spectra of 12 Galactic and 40 extragalactic sources. For each source, we have estimated column densities for N i, N ii, N iii, N v, N vi, and N vii ionic species, which trace the cold, warm, and hot phases of the local Galactic ISM. We have found that the cold-warm component column densities decrease with the Galactic latitude, while the hot component does not. Moreover, the cold column density distribution is in good agreement with UV measurements. This is the first detailed analysis of the nitrogen K-edge absorption due to ISM using high-resolution X-ray spectra.